Validity of Illegal SIM Card Sales Under Article 1320 Indonesian Civil Code - Aditiya; Mutia Cherawaty Thalib; Sri Nanang Meiske Kamba (Legtimacy: Journal of Law and Islamic Law, 2026)
This study critically examines the validity of illegal SIM card sales agreements under Article 1320 of the Indonesian Civil Code. The proliferation of digital telecommunications has triggered unlawful registrations using manipulated personal data, creating fundamental legal flaws in consumer contracts. Employing a normative juridical methodology, this research demonstrates that such illicit transactions categorically fail to fulfill the objective requirement of a lawful cause. Consequently, these defective agreements are deemed strictly null and void, mandating total restitution. Furthermore, the ensuing legal liability is multidimensional: civil liability burdens negligent sellers, strict administrative sanctions apply to telecommunication operators, and severe criminal penalties target data falsifiers. Injured consumers retain absolute rights to seek comprehensive compensation through robust dispute resolution mechanisms or formal civil litigation. Ultimately, this study highly recommends strengthening statutory regulations and harmonizing the Civil Code, Consumer Protection Law, and Personal Data Protection Law to ensure absolute national legal certainty for all citizens.